Hiding in the echo chamber: fact-Checking failures and individual tactics of accuracy determination on WhatsApp in India. Issue 2 (4th March 2022) - Kanthawala, Shaheen; Maddox, Jessica
ABSTRACT: During a time of heightened political polarization in India, use of the communication app WhatsApp skyrocketed. Alongside benefits of the app come a slew of dangerous outcomes, such as the proliferation of misinformation on the chat-based app. To this end, we conducted 19 semi-structured, in-depth interviews with Indian users of WhatsApp over the age of 40. The aim of study was to examine how WhatsApp users engage with the platform and the content they access through it in order to mediate through political polarization at an already divisive time." Our results yielded three overarching themes: First, participants rarely engage in accuracy determination tactics. Second, they expressed familiarity with politically polarizing content but claimed not to engage with it. Third, they expressed intense hopes for future effective content moderation on WhatsApp. By applying cultivation theory to these insights, we examine how the app creates a reality for its users based on media socialization and the truth effect . Our participants' insights and our subsequent analysis challenge the top-down-centric approach of many technology companies and governments to curb misinformation. We instead propose a holistic approach that better advances our understanding of the misinformation ecosystem.